Dominance of Emerging G9 and G12 Genotypes and Polymorphism of VP7 and VP4 of Rotaviruses from Bhutanese Children with Severe Diarrhea Prior to the Introduction of Vaccine - Wangchuk, Sonam (Public Library of Science, 2014)
A prospective study was performed to determine the molecular characteristics of rotaviruses circulating among children aged <5 years in Bhutan. Stool samples were collected from February 2010 through January 2011 from children who attended two tertiary care hospitals in the capital Thimphu and the eastern regional headquarters, Mongar. The samples positive for rotavirus was mainly comprised genotype G1, followed by G12 and G9. The VP7 and VP4 genes of all genotypes clustered mainly with those of neighboring countries, thereby indicating that they shared common ancestral strains. The VP7 gene of Bhutanese G1 strains belonged to lineage 1c, which differed from the lineages of vaccine strains. Mutations were also identified in the VP7 gene of G1 strains, which may be responsible for neutralization escape strains. Furthermore, we found that lineage 4 of P[8] genotype differed antigenically from the vaccine strains, and mutations were identified in Bhutanese strains of lineage 3. The distribution of rotavirus genotypes varies among years, therefore further research is required to determine the distribution of rotavirus strain genotypes in Bhutan.